Strategi Negosiasi Masyarakat Muslim Pedesaan Atas Tradisi Perkawinan Lusan (Studi Kasus Di Desa Duri Kecamatan Slahung Kabupaten Ponorogo) - Musthofa, Arifin; Dwijayanto, Arik (Institut Agama Islam Sunan Giri Ponorogo, 2020)
The custom of prohibiting marriage after marriage has become its own dynamic, especially for the current generation. However, the ban on the customary marriage after marriage can still be implemented with several efforts and alternatives that are in accordance with applicable customs. This is the background of this research. The purpose of this study is to find out the rationalization/reasons of the people of Duri Village in carrying out the tradition of marriage after marriage, to describe the practice of marriage after marriage in Duri Village, Slahung District, Ponorogo Regency, to analyze the strategy in carrying out the marriage after marriage, and to be able to carry out the marriage without any obstacles. Data collection techniques in this study by interview, observation, documentation. Data analysis techniques in this study using data reduction, data presentation, drawing conclusions / verification. The results of this study indicate that the prohibition of late marriage in Duri Village is still firmly held by the community. However, the practice of marriage after marriage is carried out in the presence of ruwatan. As a negotiation strategy regarding the existence of marriages, the community held a ruwatan to find children, there was no female guardian, there was no term besanan. Keywords: Negotiation Strategy, Rural Muslim Community, Tradition, Marriage.